Addressing health corruption during a public health crisis through anticipatory governance: Lessons from the COVID-19 pandemic - Alejandro Gonzalez-Aquines; Alejandro Gonzalez-Aquines; Iwona Kowalska-Bobko (Frontiers Media S.A., 2022)
Corruption in the health sector costs over 500 billion USD annually, weakening health system preparedness and response to health crises like the COVID-19 pandemic. The lack of resources to deal with a shock limits the capacity to protect the population, exposing them to a greater risk of infection and mortality. There is an urgent need to improve health policy to reduce corruption in the health sector during times of crisis. This article aims to propose a prepare and response strategy to address corruption during times of health crises. We first explore the inherent characteristics of health systems that make them vulnerable to corruption and present the different faces corrupt practices take. We then explain why anticipatory governance is fundamental in addressing corruption in health systems and draw upon examples of corruption during COVID-19. Finally, we conclude by proposing that anticipatory governance could decrease the impact of corruption during health crises by increasing the availability of resources required to improve the population's health.